Comparative Analysis of the Different Dyes’ Potential to Assess Human Normal and Cancer Cell Viability In Vitro under Different D/H Ratios in a Culture Medium - I. A. Zlatskiy; A. V. Zlatska; N. V. Antipova; S. A. Dolenko; I. M. Gordiienko; O. S. Gubar; R. G. Vasyliev; D. A. Zubov; S. N. Novikova; A. V. Syroeshkin (The Scientific World Journal)
In this study, using new approach (laser diffraction + biological dyes), we have demonstrated the decrease of cells viability in vitro in the deuterated growth medium, whereas in the deuterium-depleted medium, there was an increase of cell viability. We have also found that not all dyes are equally sensitive to the D/H ratios in the culture medium (system) as well as to the different cell types (cancer vs normal cells).